Membangun Ketahanan Ekonomi Melalui Pendampingan Perilaku Hidup Bersih dan Sehat di Ekowisata Desa Asinan Danau Rawa Pening - Pambudi, Rakhmat Dwi; Sumaga, Amalia Salsa; Wijayanti, Anis Fitria; Tasya Islami, Laily (Jurnal Ilmiah Pangabdhi, 2023)
The Covid-19 pandemic demands the implementation of Clean and Healthy Behavior in various aspects of life, including in the tourism sector. The purpose of this community service activity is to increase understanding and application of Clean and Healthy Behavior in the Asinan Danau Rawa Pening Village Ecotourism. The targets of this activity are MSME actors, visitors, and the community around the Asinan Village Ecotourism. The types of activities carried out are outreach, mentoring and provision of disinfection kits. In its implementation, this activity uses the ABCD (Asset Based Community Development) approach. Based on the results of the community service activities carried out, it can be concluded that public understanding and awareness of clean and healthy living behavior still needs to be improved. Socialization of Clean and Healthy Behavior to the community and MSME actors is very important to continue, because it will be beneficial to improve the quality of public health, create environmental sustainability, and contribute to increasing the economic resilience of the Asinan community Village.